Advanced X-by-Wire Technologies in Design, Control and Measurement for Vehicular Electrified Chassis - Li, Yong; Xu, Xing; Zhang, Lin; Qin, Yechen; Lu, Yang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advanced X-by-wire technologies for vehicular electrified chassis play an essential role in the development of new energy intelligent vehicles, which is the inevitable choice for intelligent vehicles in the future. This technology is involved in mechanical engineering, electronic and electrical engineering, computer technology, control engineering, signal processing, and artificial intelligence. Advanced electrified chassis control technology transmits control signals through cables and acts directly on the actuator to implement corresponding actions. The application of X-by-wire technologies for vehicular electrified chassis has changed the complex mechanical connections among actuators and hydraulic and pneumatic equipment in the past, greatly promoting energy efficiency, integration, and intelligence. This reprint focuses on advanced X-by-wire technologies in strong reliability design, modeling, integration control, thermal management, energy management, fault diagnosis, and fault-tolerant control with the vehicular electrified chassis. Therefore, the aim of this reprint was to solicit recent advanced X-by-wire technologies for vehicular electrified chassis.